2005
DOI: 10.1128/jvi.79.6.3525-3535.2005
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation among Murine Cytomegalovirus US22 Proteins Encoded by Genes M139, M140, and M141

Abstract: The murine cytomegalovirus (MCMV) proteins encoded by US22 genes M139, M140, and M141 function, at least in part, to regulate replication of this virus in macrophages. Mutant MCMV having one or more of these genes deleted replicates poorly in macrophages in culture and in the macrophage-dense environment of the spleen. In this report, we demonstrate the existence of stable complexes formed by the products of all three of these US22 genes, as well as a complex composed of the products of M140 and M141. These co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 26 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…3A and B) (18). The use of anti-␣-tubulin antibodies in the current study revealed that this site is adjacent to the microtubule organizing center (MTOC).…”
Section: Vol 83 2009 Role Of M140 In MCMV Capsid Assembly In Macropmentioning
confidence: 99%
See 4 more Smart Citations
“…3A and B) (18). The use of anti-␣-tubulin antibodies in the current study revealed that this site is adjacent to the microtubule organizing center (MTOC).…”
Section: Vol 83 2009 Role Of M140 In MCMV Capsid Assembly In Macropmentioning
confidence: 99%
“…The M139, M140, and M141 early gene products form at least three stable complexes that colocalize to a perinuclear cis-Golgi region in infected macrophages (18). Sequence analysis of the three genes does not reveal any consensus functional domains, with the exception of a putative nuclear localization sequence within M139 and M141 (15).…”
Section: Macrophages Are An Important Target Cell For Infection With mentioning
confidence: 99%
See 3 more Smart Citations